PENGARUH PEMBELAJARAN SENI PAPERCRAFT TERHADAP KEMAMPUAN MOTORIK HALUS ANAK TUNADAKSA - Hengky Triwijaya,; Wiwik Dwi Hastuti (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2014)
The purpose of this was to describe the implementation process of the papercraft art learning and to determine papercraft art learning influence on soft motor skills ability of handicaped child. The research used an experimental method with a Single Subject Research (SSR) multiple baseline cross variables design. Data were analyzed by using a visual analysis of graphic technique. The results of research showed a papercraft art learning influence on soft motor skills. This condition on soft motor skills, was shown by many trials of cutting, folding and sticking ability evaluation at baseline (A) condition and intervention (B) condition. Conclusion of this research is the soft motor ability of children before papercraft art learning given that the baseline phase of skills motor skills children increased an average of one trial. Soft motor ability after papercraft art learning given that on average the intervention phase average increase of two trial. Papercraft art learning techniques as cutting, folding and sticking can affect soft motor skills of hadicaped child with changes in each session of the intervention phase.Tujuan dari ini adalah untuk mendeskripsikan proses pelaksanaan pembelajaran seni papercraft untuk menentukan seni papercraft dapat mempengaruhi kemampuan motorik halus. Penelitian ini menggunakan metode eksperimen dengan Single Subject Research (SSR) beberapa desain variabel lintas awal. Data dianalisis dengan menggunakan analisis visula. Hasil penelitian menunjukkan pengaruh pembelajaran seni papercraft pada keterampilan motorik halus. Kondisi ini pada keterampilan motorik halus, ditunjukkan oleh latihan, melipat dan menempel. Kesimpulan dari penelitian ini adalah kemampuan motorik halus anak-anak dapat meningkat.Teknik Papercraft ini dilakukan dengan pemotongan, melipat dan menempel dapat mempengaruhi keterampilan motorik halus anak hadicaped dengan perubahan di setiap sesi fase intervensi.